Yoga for psychological outcomes and quality of life in non-cystic fibrosis bronchiectasis: a controlled study - Hei, Lele; Zhang, Yue; Si, Yanyan; Bai, Lili (Frontiers in Psychiatry, 2025)
ObjectivesThis study explored the potential impact of a structured yoga program over an 8-week period on aspects of psychological health and health-related quality of life (HRQoL) among individuals diagnosed with non-cystic fibrosis bronchiectasis.MethodsA prospective, controlled clinical study was carried out from January 2023 to January 2024. Sixty-nine adults with clinically stable non-cystic fibrosis bronchiectasis were recruited and assigned randomly to either a yoga intervention group (n = 24) or a control group receiving standard care (n = 45). The yoga group engaged in supervised online sessions three times weekly, while the control group continued with routine clinical management without any added exercise regimen. HRQoL was measured using the Quality of Life-Bronchiectasis (QOL-B) questionnaire. Psychological variables were assessed through the Short Form-36 (SF-36), Hospital Anxiety and Depression Scale (HADS), and the Perceived Stress Scale-10 (PSS-10). Evaluations took place at baseline and after the 8-week period. Statistical analyses were applied based on data distribution, with significance determined at a threshold of P < 0.05.ResultsParticipants undergoing yoga demonstrated notable improvements in select QOL-B domains, particularly in areas such as respiratory symptoms, emotional aspects, and vitality, when compared to the control group (P < 0.05). SF-36 results suggested gains in both physical and mental summary scores in the yoga group; however, the control group showed no comparable changes. Psychological assessments indicated reduced anxiety and depression scores, as well as lower perceived stress levels, in those practicing yoga (P < 0.01). Group comparisons suggested that the yoga intervention was more favorable than standard care in influencing the measured outcomes. However, the study was limited by its relatively small sample size, short intervention duration, and reliance on self-reported data, which may affect the generalizability and long-term sustainability of the observed benefits.ConclusionAn 8-week structured yoga program may contribute to improvements in psychological well-being and quality of life among patients with non-cystic fibrosis bronchiectasis. Yoga might represent a complementary approach alongside conventional management, though its role requires additional exploration.